Is malaria elimination a distant dream? Reconsidering malaria elimination strategies in Zimbabwe - Elliot Mbunge (Public Health in Practice, 2021)
Malaria remains a public health problem decimating vulnerable populace especially in resource-constrained areas in Zimbabwe. Significant progress towards malaria elimination has beenik made in the previous decades through intensified and improved malaria control measures such as indoor residual spraying (IRS), distribution of long-lasting insecticidal nets (LLIN), artemisinin-based combination therapy and administration of intermittent preventive treatment in pregnancy. However, the outbreak of pandemics like coronavirus disease (COVID-19), cyclones and tropical storms, lack of funding, porous political environment, dearth of resources for vector control, changes in vector behaviour, vector resistance to insecticides, community behavioural change and lack of feasible and sustainable digital technologies for managing malaria control interventions retards progress made towards malaria elimination. Also, arbitrary political environment and unstable economic situation often interfere with health programmes which subsequently lead to malaria outbreaks. Most recently, the country recorded a sharp increase in malaria incidences in malaria-endemic areas especially during the pandemic due to some factors such as movement restrictions, temporary cancellation of IRS activities, delayed delivery of IRS chemicals and recursive lockdown. Therefore, we propose ways to mitigate future malaria outbreaks and advocate for reconsidering malaria elimination strategies to addresses emerging challenges in eradicating malaria in Zimbabwe.